Laminations and Microgranule Formation in Pediatric Glomerular Basement Membranes. (1st October 2014) - Craver, Randall; Crespo-Salgado, Janice; Aviles, Diego
<x xml:space="preserve">Abstract</x> Glomerular basement membrane (GBM) splitting, laminations, and microgranular formation are classically encountered with Alport disease, but can be found in other glomerular diseases. We found moderate to marked GBM laminations/microgranular formations in 51 of 724 (7%) pediatric diagnostic renal biopsies. These included 12 Alport disease, 12 thin basement membrane disease (TBM), 13 mesangial hypercellularity (MH), 6 focal segmental glomerulosclerosis (FSGS), and 8 other diseases. Follow-up demonstrated progression in most of the Alport disease and FSGS, as expected, but also in 40% of TBM and 30% of MH. Basement membrane laminations/microgranular formations are not specific for Alport disease, may represent a non-specific injury, and may herald a progressive clinical course.